2017
DOI: 10.21276/apjhs.2017.4.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between social support during the postpartum period and the level of readiness for hospital discharge

Abstract: This is a descriptive study, aimed at determining the correlation between social support in the postpartum period and the level of readiness for hospital discharge. Methods: The study was conducted with 291 women during their stay in the postpartum unit of a public hospital in eastern Turkey. The participants to be included in the study sample were selected using random sampling. The study data were collected using an individual introduction form RHDS-NMF, and the MSPSS.The researchers used the chi square test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Coffey and McCarthy (2013) found that lack of support at home hindered preparation for discharge (Coffey and Mccarthy, 2013). Tahan et al. (2017) stated that the mean score of social support during the postpartum period was higher in those who felt ready than in those who were not prepared for discharge ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coffey and McCarthy (2013) found that lack of support at home hindered preparation for discharge (Coffey and Mccarthy, 2013). Tahan et al. (2017) stated that the mean score of social support during the postpartum period was higher in those who felt ready than in those who were not prepared for discharge ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Coffey and McCarthy (2013) found that lack of support at home hindered preparation for discharge (Coffey and Mccarthy, 2013). Tahan et al (2017) stated that the mean score of social support during the postpartum period was higher in those who felt ready than in those who were not prepared for discharge (p < 0.05). Thus, women's RHD was affected by their perceived social support, and their level of readiness increased with the level of provided social support (Tahan et al, 2017).…”
Section: Defining Attributesmentioning
confidence: 99%